Development of Coffee Production in Kepahiang - Anzori Tawakal (Jurnal Fokus Manajemen, 2022)
The purpose of this study is to increase the income of coffee farmers in Kepahiang Regency, increase promotion and branding of coffee in Kepahiang Regency at the national and international levels, increase the knowledge of farmers and field workers about coffee cultivation technology farmers. This research includes descriptive research, which explains factual phenomena conceptually. The factual findings from the research are verified by existing theoretical concepts. The approach taken was a survey of a number of respondents who were selected based on certain criteria. The unit of analysis used in this study was coffee farmers, stakeholders, and related stake holders as well as the local government of coffee-producing districts, coffee business actors/traders in Kepahiang district. Optimizing the cooperation network, both the government and related stockholders; Optimizing priority programs for superior coffee production using special economic zones; Following up on the MOU with KPTIK and Bengkulu Provincial Government to make Bengkulu a national coffee area; Fighting for Bengkulu to get HAKi to increase regional competitiveness; Increased production of superior coffee already has sufficient value in the eyes of consumers;